Research of Welding P91 steel with Shielded Metal Arc Welding (SMAW) and Gas Tungsten Arc Welding (GTAW) processes - Han, Le Duy (Old Journal, 2017)
P91 steel (9Cr-1Mo-V-Nb-N) was developed from the mid-1970s by the Oak Ridge National Laboratory (ORNL) under the auspices of the USA government. The challenges encountered when welding this steel alloys such as mechanical properties of heat affected zone (HAZ) is high. This will affect the ability of the structure to work in conditions with high temperature and high pressure. This article will focus on the study of theory and experiment in order to overcome this phenomenon, through the search for welding parameter ranges and reasonable heat treatment to improve toughness in HAZ as well as quality assurance of weld.